EFFECT OF CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE OF LISTED OIL AND GAS FIRMS IN NIGERIA - Ikechukwu Agu, Charles; Godwin Ogbogu Nwankwo, Bobby; Anastasia Aniekwe, Mmesoma (African Journal of Social and Behavioural Sciences, 2026)
This study investigated the effect of Corporate Social Responsibility (CSR) on the financial performance of listed oil and gas firms in Nigeria from 2014 to 2023. Specifically, it examined how funds allocated to human training, health and education; infrastructure and development; and associations affect the net profit margin of these firms. The population of the study comprised nine listed oil and gas firms in Nigeria. Employing an Ex-Post Factor research design, the study used secondary data extracted from audited annual reports of five selected oil and gas companies listed on the Nigerian Exchange Group (NGX). The data were analyzed using descriptive statistics and ordinary least squares (OLS) regression with E-Views 11 software. The findings are: Funds for human training, health, and education have a positive but non-significant effect on Net Profit Margin of listed oil and gas firms in Nigeria (β = 0.00000008; p = 0.2027); Funds for infrastructure and development have a positive and significant effect on Net Profit Margin of listed oil and gas firms in Nigeria (β = 0.00000009; p = 0.0001); Funds for associations have a positive but non-significant effect on Net Profit Margin of listed oil and gas firms in Nigeria (β = 0.00000002; p = 0.5319).In conclusion, CSR spending alone does not automatically translate into enhanced profitability; rather, the economic effect of CSR appears to depend on the nature of the investment and perhaps the visibility, scale, or strategic alignment of those activities with core business goals. The study recommends that Executive Management should increase funding allocations to infrastructure and development projects, especially those that serve both community and operational needs (e.g., roads, energy access, water). These investments should be scaled and strategically aligned with business operations to enhance both community goodwill and profitability.